Evaluation of Performance of Farmer Producer Organizations (FPOs) in Medak District of Telangana State: A Case of Belauri Municipality - C.D. Amitha,; B. Savitha,; Rani, V. Sudha; Rani, P. Laxminarayana (Journal of Agricultural Extension Management, 2022)
Farmer Producer Organizations (FPOs) are emerging as a structure, which is indispensable in the development arena of agriculture and rural development programmes. In this article an attempt has been made to study the performance of FPOs. The study compares the performance of three selected FPOs on identified performance indicators. Three FPOs were selected randomly from three different promoting institutes viz., Suraksha Farmer Producer Company Ltd (SFPCL) promoted by Centre for Sustainable Agriculture (CSA) an independent research organization, Marpalli Kisan Kranthi Producer Company Ltd (MKKPCL) promoted by Vrutti NGO and Siddipet Kisan Agro Farmers Producer Company Ltd (SKAFPCL) promoted by ICRISAT. An ex-post facto research design was adopted for the study with a sample of 90 producer members, covering three FPOs in erstwhile Medak district of Telangana state. From the analysis, it was found that SFPCL was rated as average while, MKKPCL was rated as a poor performing FPO and performance of SKAFPCL was rated as good. This can be attributed to the institutional support received by the FPOs from their POPIs. Overall, the performance of FPOs was average to poor. This was due to insufficient knowledge on the business concept of FPOs among farmers and their inability to generate capital to carry out activities and provide services to their members.